Analysis of the problems and prospects of the tourism industry in Myanmar - Soe Thinzar Hlaing; Tang, John C.S.; Sununta Siengthai; Donyaprueth Krairit; Government of France - AIT Fellowship (Pathum Thani, Thailand : Asian Institute of Technology, 2006)
For many developing countries, tourism is perceived as a fast track to economic growth. It is widely assumed that tourism development requires less investment than other industries; and they believe tourism to be an effective means of creating job opportunities and increasing local income. Tourism in general faces fewer constraints in the form of market protectionism than is the case with manufacturing, for instance. Further, the technological and human resource requirements of tourism are in general much lower and more easily accessible. Myanmar has long ascribed to this point of view. The myriad economic and other benefits which may be gained from tourism help explain why the Myanmar government has been keen on promoting tourism. Myanmar may have excellent tourism potential, with a rich diversity of natural, cultural and other heritage assets. The strong point of Myanmar tourism is that it possesses natural resources, climate, culture, history, and ethnicity that exert a pull on visitors making it a fascinating tourism destination However, Myannlar has yet to make a significant impact in this industry that since the industry is underdeveloped as a result of many structural constraints. Its political instability, governmental policies and internal unrest have been the subject of international condemnation. Subsequently, sanctions imposed by various international governments have politically and economically isolated Myanmar. These factors combined with other external conditions pose a major threat to the country's tourism industry. Nevertheless, new trends in world tourism such as an increase in regional cooperation on tourism, the growth of tourism in Asia Pacific region, along with other positive tourism trends could have a positive impact on the tourism of Myanmar. The extent to which the government and the organizations can benefit from these opportunities will determine the success of tourism in Myanmar. Great effort has been put to attract visitors and put Myanmar in the mind of potential tourists. Due to these efforts, the industry is experiencing a period of growth. It has also brought in much needed foreign exchange earnings for the Country's economy. However, Myannlar laces enormous challenges in realizing the ultimate goal of being an established and well-known tourist destination. There is a good chance that tourism in Myanmar can materialize as per the painted ideal dream. In order for that to happen, the government needs to engage in reforms that would create a political and economic environment that is conducive to the development of tourism. This requires a sincere wish on the part of the `government to engage in political reforms that would encourage fairness, transparency and the promotion of hllnlan rights 1'01' the benefit of the Myanmar people
A research study submitted in partial fulfillment of the requirements for the degree of Master of Business Administration, School of Management
Research Studies Project Report (M.B.A.) - Asian Institute of Technology, 2006
Keywords: Tourism -- Myanmar